Total Knee Arthroplasty in the Younger Patient - Shah, Sapan H.; Schwartz, Brian E.; Schwartz, Aaron R.; Goldberg, Benjamin A.; Chmell, Samuel J. (The Journal of Knee Surgery, 2017)
The rate of total knee arthroplasty (TKA) utilization in younger patients (< 65 years old) is increasing. Little is known regarding demographics and in-hospital outcomes in this population. The National Hospital Discharge Survey (NHDS) database was searched using International Classification of Diseases, Ninth Revision (ICD-9) procedure codes for patients admitted to U.S. hospitals for unilateral primary TKA between 2001 and 2010. Patients were separated into young (< 65 years of age) and senior cohorts (≥ 65 years of age). ICD-9 diagnosis and procedure codes were used to identify demographics, hospital length of stay, in-hospital adverse events, mortality, and discharge disposition. Trends were evaluated by linear regression with Pearson correlation coefficient (r) and statistical comparisons were made using Student t-test and chi-square analysis. The young cohort accounted for 38.4% of TKAs performed from 2001 to 2005, increasing to 42.7% of TKAs from 2006 to 2010. They had a higher percentage of males (36.4 vs. 34.2%, p < 0.001). Rates of obesity (11.1 vs. 6.0%, p < 0.001) and morbid obesity (5.8 vs. 1.9%, p < 0.001) were significantly higher, yet they had less comorbidities (4.7 vs. 5.2, p < 0.001), and lower rates of transfusion (12.2 vs. 19.8%, p < 0.001), pulmonary embolism (PE) (0.31 vs. 0.49%, p < 0.020), and mortality (0.03 vs. 0.18%, p < 0.001). Patients < 65 years old undergoing TKA have almost double the rate of obesity of patients ≥ 65 years old. This could explain the higher rates of periprosthetic infection and aseptic mechanical failure seen in younger patients. However, the young cohort had a more favorable discharge disposition and lower mortality and risk of PE than elderly patients.
Keywords: knee; arthroplasty; epidemiology; postoperative outcomes; age